Skill and Experience gained through working in a NGOs and the project of the “Emergency shelter assistance for the most vulnerable households affected by cyclone Roanu in Bangladesh at Kutubdia Upazila in Cox’s Bazar” - Uddin, Mohammad Saleh (BRAC University, 2017)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Development Management and Practice, 2016.